2011
DOI: 10.1007/s00540-011-1236-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recovery times from rocuronium-induced muscle relaxation after reversal with three different doses of sugammadex and succinylcholine during electroconvulsive therapy

Abstract: This study demonstrates the efficacy of rocuronium-sugammadex as an alternative to SCC for muscle relaxation during ECT, and indicates that 8 mg/kg sugammadex produces equally rapid recovery from rocuronium muscular relaxation compared with spontaneous recovery from 1 mg/kg SCC during ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
3
21
0
2
Order By: Relevance
“…4 In our study, the doses of rocuronium and sugammadex used were half the dose level of that of Kadoi et al 4 The recovery times were similar to their study. 4 In our study, the doses of rocuronium and sugammadex used were half the dose level of that of Kadoi et al 4 The recovery times were similar to their study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…4 In our study, the doses of rocuronium and sugammadex used were half the dose level of that of Kadoi et al 4 The recovery times were similar to their study. 4 In our study, the doses of rocuronium and sugammadex used were half the dose level of that of Kadoi et al 4 The recovery times were similar to their study.…”
Section: Discussionsupporting
confidence: 86%
“…4 At a dose of 0.3 mg/kg, rocuronium provides optimal conditions for intubation in many patients. They compared the recovery time and time to onset of spontaneous breathing with that of 1 mg/kg of succinylcholine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the combination of rocuronium and sugammadex is a promising new clinical alternative. A single-center study showed that the efficacy of rocuronium followed by 8 mg/kg sugammadex at the end of the ECT treatment was equally effective regarding recovery time compared with succinylcholine alone 33,75…”
Section: Specific Indicationsmentioning
confidence: 99%